KONSEP GIRI DAN GIMU YANG TERCERMIN DALAM DRAMA FREETER, IE WO KAU KARYA SUTRADARA KONO KEITA DAN JOHO HIDENORI - PRATIWI, ADE PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Society is a group of people who created a culture. In a culture there is reciprocity norm that someone should help those who have helped him. In Japan, it’s called giri and gimu. Giri and gimu many contained in the literature. In this anlysis, the aouthor use a television drama because drama has a different form from novels or short stories. Drama that used is a family drama titled Freeter, Ie Wo Kau. This drama tells the story of a freeter that trying hard to restore his mother’s smile who was ill. To find giri and gimu in Freeter, Ie Wo Kau drama, the author uses the theory of antropological literature by examining the interaction based on figures in the form of images and conversations, as well as using the theory of mise en scene as the supporting theory. The purpose of this study was to describe the giri and gimu concept that reflected in the drama Freeter, Ie Wo Kau. Result of this study indicate that this drama have giri to the world, giri to the name, gimu nnmu and gimu koo. Giri to the world contained in the Seiichi for Noriko and Seiji for Ooetsu. Giri to the name contained in the name of Ayako, Seiji and Chiba. Gimu koo contained in Seiji and Sumiko for his family. Gimu ninmu contained in Chiba and workers. For subsequent studies suggester to extend the analysis with a different approach and issues. Hopefully, this research can help learners and enthusiasts of Japanese culture to understand Japanese culture, particularly the concept of reciprocation. Keyword: drama, society, reciprocity norm, giri, gimu